Changes in serum creatinine, uric acid, creatine kinase, and glomerular filtration rate in street runners. http://dx.doi.org/10.5007/1980-0037.2013v15n1p71 - Anderson Pontes Morales; Ronaldo Nascimento Maciel; Felipe Sampaio Jorge; Nilo Terra Arêas Neto; Daniela de Carvalho Cordeiro; Maria Auxiliadora Siqueira Viana; Carlos Jorge Logullo Oliveira (Universidade Federal de Santa Catarina, 2013)
The strategies adopted by street runners during races are influenced by the distance of the race as well as the technical and physical condition levels of the runners. The objective of this study was to examine the biochemical effects of Creatinine (C), Uric Acid (UA), Creatine Kinase (CK), and of the Glomerular Filtration Rate (GFR) caused by a 6-kilometer street race. The participants (n=15) were all male athletes (40.53±8.65 years) and were divided into 3 groups: Group 1 Best Times (G1MT) n=5, Group 2 Intermediate Times (G2TI) n=5, Group 3 Worst Times (G3PT) n=5. Blood samples were collected 30 minutes before and immediately after the race. The data was analyzed by Two-Way ANOVA, Wilcoxon, and Mann Whitney. Significant levels were considered as (p<0.05). The results showed that there were significant intragroup increases in serum activities of (C) in G1MT pre: 1.18±0.04 mg.dL-¹ post: 1.60±0.15 mg.dL-¹; G2TI pre: 1.04±0.15 mg.dL-¹ post: 1.56±0.21 mg.dL-¹; G3PT pre 1.08±0.13 mg.dL-¹ post 1.52±0.32 mg.dL-¹, and in (AU) G1MT pre: 3.80±0.75 mg.dL-¹ post 4.56±0.94 mg.dL-¹; G2TI pre 4.36±1.62 mg.dL-¹ post 5.0±1.69 mg.dL-¹; G3PT pre 4.62±1.08 mg.dL-¹ post: 5.42±0.86 mg.dL-¹, while CK and GFR did not show any significant difference.